2010
DOI: 10.1039/c0dt00532k
|View full text |Cite
|
Sign up to set email alerts
|

Diverse reactions of sterically-protected 1,3-diphosphacyclobutane-2,4-diyls with hydride

Abstract: Hydride-induced elimination of resonance stabilized substituents from a phosphorus center of 1,3-diphosphacyclobutane-2,4-diyls leads to the formation of versatile cyclic phosphaallyl anions that are useful for the construction of various electrophile-modified biradical species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…A DFT‐optimized structure of 5a [Gaussian 09 program, Becke, three‐parameter, Lee–Yang–Parr (B3LYP)/6‐31G(d)] is comparable to the X‐ray structure of 4d and complete active space self consistent field CASSCF(2,2)/6‐31G(d) calculations indicate an occupation in the highest occupied molecular orbital (HOMO) (#139) orbital with 1.88 electrons. In the 31 P NMR spectrum, 4a shows the typical AB pattern signals that are similar to the unsymmetrical P‐heterocyclic biradicals known to us so far . Chemical shifts of the PEt and PMe groups are similar to symmetric 4c (see Experimental Section) and 4d , respectively, and a similar 2 J PP constant for 4a to 4b is observed.…”
Section: Resultssupporting
confidence: 58%
“…A DFT‐optimized structure of 5a [Gaussian 09 program, Becke, three‐parameter, Lee–Yang–Parr (B3LYP)/6‐31G(d)] is comparable to the X‐ray structure of 4d and complete active space self consistent field CASSCF(2,2)/6‐31G(d) calculations indicate an occupation in the highest occupied molecular orbital (HOMO) (#139) orbital with 1.88 electrons. In the 31 P NMR spectrum, 4a shows the typical AB pattern signals that are similar to the unsymmetrical P‐heterocyclic biradicals known to us so far . Chemical shifts of the PEt and PMe groups are similar to symmetric 4c (see Experimental Section) and 4d , respectively, and a similar 2 J PP constant for 4a to 4b is observed.…”
Section: Resultssupporting
confidence: 58%
“…The smaller pyramidalization of the t BuP phosphorus atom and shorter P( t Bu)–C1/C2 bonds would correlate with the electron‐donating character of the t ‐butyl group. The 31 P NMR spectroscopic data show the larger‐field chemical shift of the t BuP group,,,, which might be due to the canonical formula. The molecular structure of 8 indicated that the isopropylamino group increases the electron‐donating property of the P‐heterocyclic chromophore .…”
Section: Properties Of the Directly Arylated 13‐diphosphacyclobutanementioning
confidence: 96%
“…Preparation of CBA via the reductive P–C cleavage of 1,3‐diphosphacyclobutane‐2,4‐diyl was also developed. Reaction with lithium aluminum hydride (LiAlH 4 ) induced removal of the XCH 2 unit (X=aryl, alkenyl, alkynyl, carbonyl) to generate the t Bu‐substituted diphosphacyclobutenyl anion CBA‐1 ( vide infra ) . On the contrary, the predominant reductive cleave of the t Bu–P bond in the 1,3‐diphosphacyclobutane‐2,4‐diyl was induced by t ‐butyllithium to generate the corresponding CBA that are not easy to prepare from 2 together with the hydride‐loaded byproduct (Scheme ) …”
Section: Chemistry Of 13‐diphosphacyclobuten‐4‐yl Anion (Cba)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we investigated the effects of the arylmethyl substituent on the solid-state properties of open-shell singlet P-heterocycles. First, we screened several arylmethyl substituents and found that in addition to the previously synthesized 3 and 4, [13] 2-anthrylmethyl-and 2-thieno[3,2,-b]thiophenylmethyl-substituted 1,3-diphosphacyclobutane-2,4-diyls were suitable for use in p-type FET devices. To understand the semiconductor characteristics of the most promising diyls in detail, we evaluated their hole transfer integrals (V) and reorganization energies (l) based on density functional theory (DFT) calculations and X-ray crystallographic analyses, then estimated their hole hopping rates (W) and diffusion coefficients (D).…”
Section: Introductionmentioning
confidence: 99%